Effects of video-feedback correction of infant–mother interaction on two-years-olds’ behaviour - Kalinauskienė, Lina; Čekuolienė, Danguolė; Kusakovskaja, Inna; Kiltanavičiūtė, Vaida (Psichologija, 2009)
Objective. A andomized control trial examined the effects of short-term, interaction focused and attachment-based video-feedback intervention (VIPP, Juffer et al., 2008) in infancy on children’s behaviour problems at the age of two years.Design. Intervention effect on children‘’s behaviour problems was assessed in a sample of N = 85 mother–infant dyads (only first-born healthy infants, living in intact families participated). Intervention effect on children’s behaviour problems was evaluatedin non-clinical, middle-class Lithuanian mothers by comparing three groups of mother–infant dyads: low-sensitive mothers, who participated in the intervention (N = 21), low sensitive mothers who did not participate in the intervention (N = 21), and a groupof sensitive mothers with a higher sensitivity (N = 43) who did not take part in the intervention.Intervention. The VIPP intervention consisted of five monthly sessions and was implemented between the 7th and 12th months of infant’s age. The intervention was conducted by two clinical psychologists after an extensive training.Method. Maternal sensitivity was evaluated from video-record of the free play sessions using the Ainsworth sensitivity scale. Children’s behaviour problems were assessed using CBCL 1/2-5 (Achenbach and Rescorla, 2000). Infants’ positive and negativereactivity (temperament) from observational data and maternal daily stress (Crnic and Greenberg, 1990) were assessed additionally.Results. Children of the intervention group mothers received similar scores on behaviour problems scales as did control group mothers and mothers with a higher sensitivity. Maternal sensitivity in all groups of infant–mother dyads did not correlate significantly with the scores on children’s internal, external and total behaviour problems’ scales. Maternal daily stress (related to child care) significantly correlated with children’s behaviour problems in the control group. In the group of mothers with higher sensitivity, family income, fathers’ age and occupation significantly correlated with the later children’s behaviour problems. We could speculate that in the low sensitive mothers’ intervention group we maybe did not find a correlation between maternal daily stress (related to child care) and later children’s behaviour problems, because the intervention served as a buffer for these mothers, while in low-sensitive mothers of the control group the mentioned correlation was moderate.Conclusion. Children’s behaviour problems at two years were not significantly affected by intervention in infancy.
Keywords: mother’s sensitivity to her child’s signals; child behaviour problems; mother–infant interaction correction; video analysis method